(untitled) (Web of Technology: Multidimensional Research Journal, 2025)
This article presents a scientific analysis of the role of the Chiroqchi principality, which was important in the political system of the Bukhara Emirate in the late Middle Ages, and its role in political processes. The article, based on historical sources, archival documents, and academic research, studies in detail the economic, military, political, and socio-educational potential of the Chiroqchi region. In particular, the development of the Chiroqchi principality as an independent territorial form of government in the emirate’s governance system, its relations with the central government, and its role in internal political struggles are analyzed. The article provides evidence of the appeals of the Chiraqchi beys to the emir, their activity in managing regional economic resources, and their role in ensuring military and social stability through historical documents and letters from the National Archives of Uzbekistan. It also examines the cultural and religious significance of the Chiraqchi region, its role in maintaining social stability in society through local madrasahs and religious centers. This study is of significant scientific importance not only in shedding light on the complexity of the territorial administration of the Bukhara Emirate, but also in a deeper understanding of the development of political institutions in the history of Central Asia. This comprehensive analysis of the historical role and political significance of the Chiraqchi bey, based on a thorough study of historical sources, makes a significant contribution to modern scientific research.